Keystone Arctic paleoceanographic proxy association with putative methanotrophic bacteria - Bernhard, Joan M.; Panieri, Giuliana (Scientific Reports, 2018)
Source at https://doi.org/10.1038/s41598-018-28871-3 . Licensed CC BY-NC-ND 4.0. Foraminifera in sediments exposed to gas-hydrate dissociation are not expected to have cellular adaptations that facilitate inhabitation of chemosynthesis-based ecosystems because, to date, there are no known endemic seep foraminifera. To establish if foraminifera inhabit sediments impacted by gas-hydrate dissociation, we examined the cellular ultrastructure of Melonis barleeanus (Williamson, 1858) from the Vestnesa gas hydrate province (Arctic Ocean, west of Svalbard at ~79 °N; ~1200-m depth; n = 4). From sediments with gas hydrate indicators, living M. barleeanus had unusual pore plugs composed of a thick, fibrous meshwork; mitochondria were concentrated at the cell periphery, under pore plugs. While there was no evidence of endosymbioses with prokaryotes, most M. barleeanus specimens were associated with what appear to be Type I methanotrophic bacteria. One foraminifer had a particularly large bolus of these microbes concentrated near its aperture. This is the first documented instance of bona fide living M. barleeanus in gas-hydrate sediments and first documentation of a foraminifer living in close association with putative methanotrophs. Our observations have implications to paleoclimate records utilizing this foundational foraminiferal species.